PENINGKATAN KEMAMPUAN MEMECAHKAN MASALAH DENGAN PEMBELAJARAN KONTEKSTUAL DAN PENGGUNAAN OPEN-ENDED PROBLEMS - Pitajeng, Pitajeng (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2006)
Abstract For most Elementary School students, problem solving is the most difficult topic. Therefore, we have to use an instructional approach that is effective to increase the student's problem solving ability. Contextual approach and the use of open-ended problems are expected to be effective to increase problem solving ability. This research is intended to investigate whether the approaches are more effective than the traditional one. The data are analyzed and tested by Analysis of variance, followed by LSD multiple comparisons. The result indicates that contextual teaching and learning approach and the use of open-ended problem are more effective than the traditional instruction and contextual teaching and learning approach is as effective as the use of open ended problems for improving problem solving ability. Keywords: contextual teaching and learning approach, open-ended problems, and problem solving ability